The Recognition of Dielectric Layered Slab from Power Measurements - Ziemelis, J.; Solovjova, T. (Elektronika ir Elektrotechnika, 2004)
To determine layered structure and slab parameters using spectrum analyser, at some frequencies was measured the reflected powerfrom the slab. The slab parameters from measurements can be obtained by numerical comparison of measurements with those calculatedfrom the model of reflected power. The calculation of slab parameters meets some problems that in this paper are solved by simulationof layered structure. To obtain unique solution of the problem the measurements must be carried out for enough number of frequencies.By simulation it is estimated contribution of measurements errors on the exactness of layers parameters determination. Ill. 5, bibl. 5 (inEnglish; summaries in Lithuanian, English, Russian).